A selective determination of copper ions in water samples based on the fluorescence quenching of thiol‐capped CdTe quantum dots. (6th August 2015) - Nurerk, Piyaluk; Kanatharana, Proespichaya; Bunkoed, Opas
Abstract: CdTe quantum dots (QDs) capped with different stabilizers, i.e. thioglycolic acid (TGA), 3‐mercaptopropionic acid (MPA) and glutathione (GSH) were investigated as fluorescent probes for the determination of Cu 2+ . The stabilizer was shown to play an important role in both the sensitivity and selectivity for the determination of Cu 2+ . TGA‐capped CdTe QDs showed the highest sensitivity, followed by the MPA and GSH‐capped CdTe QDs, respectively. The TGA‐ and MPA‐capped CdTe QDs were not selective for Cu 2+ that was affected by Ag + . The GSH‐capped CdTe QDs were insensitive to Ag + and were used to determine Cu 2+ in water samples. Under optimal conditions, quenching of the fluorescence intensity ( F 0 / F ) increased linearly with the concentration of Cu 2+ over a range of 0.10–4.0 µg/mL and the detection limit was 0.06 µg/mL. The developed method was successfully applied to the determination of Cu 2+ in water samples. Good recoveries of 93–104%, with a relative standard deviation of < 6% demonstrated that the developed simple method was accurate and reliable. The quenching mechanisms were also described. Copyright © 2015 John Wiley & Sons, Ltd.